Historical background of the formation and development of garden and park ensembles of Ukraine - Gamaliia, K. M.; Olkhovska, O. V. (History of science and technology, 2017)
The article analyzes the process of creation of landscape complexes on the territory of Ukraine in XVIII-XIX centuries in context of trends in the world garden and park construction. Historical and social preconditions that assisted development of garden and park art are lighted up.